(3JMaI GdMcGe aj fcJ GdYbhO hGdCMcGes - (3CHh HcQ eMeO Hf eMeO Hf YGUe GdCfOdSj GdZQfGWj,J (B829 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jbVi hdG jbVi Ydjg Ld TCfkG hYdG Ke GdUdGI HOhGe GdCHO Ydi GdQShd GdeUWai eMeO s
(3BNQgG (B:s
(3aUd ai GdTQcI (B: (3hGdeGd NdWg hhVYg HjO hGMO Chai GdGTJQGc eYJeO s
(3CQLhRI fSNI bOjeI ebGHdI heUMMIs
(3YfGhjf GdCHhGH hGdaUhd HGdMeQIs
(3hgj eVHhWI GdTcds
(3MhGagG eJBcdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B274s
Keywords: (3Gdabg GdeGdcjs